Determinasi Pendidikan Kewirausahaan, Penggunaan Media Sosial, dan Lingkungan Keluarga dalam Meningkatkan Minat Berwirausaha - Wirda Latifah; Khusaini Khusaini; Andi Yustira Lestari Wahab (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
Currently the number of unemployed is increasing in Indonesia, one way to reduce the unemployment rate is by entrepreneurship. However, those who become entrepreneurs are relatively few. This study intends to examine the impact of entrepreneurship education, use of social media, and family background on entrepreneurial intentions. We utilized of 274 samples unit with simple random technique. The online questionnaires were utilized to collecting data. The multiple regression results showed that entrepreneurship education, using of social media, and family background partially had a positively significant impact on the entrepreneurial intention of SMKN 9 Tangerang Regency students. This research has implications that entrepreneurship education wants to further increase the variety and use of social media by students to encourage growing intention in entrepreneurship